Vasoregulating endothelial function in essential arterial hypertension and chronic heart failure - Ya. I. Kots; E. H. Denisov; R. Z. Bakhtiyarov; N. V. Maslova (Российский кардиологический журнал)
Mechanisms of vascular tonus regulation in patients with essential arterial hypertension (EAR) and chronic heart failure (CHF) were examined by high-definition ultrasound method. EAH patients demonstrated substantially disturbed endothelium-dependent mechanisms of vascular tonus regulation, with intact endothelium-independent mechanisms. In CHE individuals, both endothelium-dependent and independent vascular reactions were disturbed. The observed changes in vasomotor reactions might precede morphological changes in vascular wall.